2018
DOI: 10.1038/s41422-018-0072-0
|View full text |Cite|
|
Sign up to set email alerts
|

Suppression of m6A reader Ythdf2 promotes hematopoietic stem cell expansion

Abstract: Transplantation of hematopoietic stem cells (HSCs) from human umbilical cord blood (hUCB) holds great promise for treating a broad spectrum of hematological disorders including cancer. However, the limited number of HSCs in a single hUCB unit restricts its widespread use. Although extensive efforts have led to multiple methods for ex vivo expansion of human HSCs by targeting single molecules or pathways, it remains unknown whether it is possible to simultaneously manipulate the large number of targets essentia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
190
1
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 215 publications
(197 citation statements)
references
References 76 publications
(158 reference statements)
4
190
1
2
Order By: Relevance
“…Recent studies have shown that loss of YTHDF2 results in enhancement of hematopoietic stem cell expansion in both mouse and human [21,22]. In contrast, depletion of YTHDF2 in AML resulted in apoptosis of AML cells [23].…”
Section: Ythdf2 Stability Is Maintained By Cdk1mentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies have shown that loss of YTHDF2 results in enhancement of hematopoietic stem cell expansion in both mouse and human [21,22]. In contrast, depletion of YTHDF2 in AML resulted in apoptosis of AML cells [23].…”
Section: Ythdf2 Stability Is Maintained By Cdk1mentioning
confidence: 99%
“…Likewise, Ythdf2 was confirmed maternally essential for early zygotic development in mice [19], and Ythdf2 depletion also negatively impacts the proliferation and differentiation of neural progenitor cells in mouse [20], suggesting broad impact of Ythdf2 on mRNA degradation in different tissues and cell types in vertebrates. The significant role of YTHDF2 in cell differentiation was further shown with depletion of YTHDF2-blocking differentiation and driving self-renewal of both mouse and human hematopoietic stem cells [21,22]. This protein is also critical to acute myeloid leukemia (AML) [23].…”
Section: Introductionmentioning
confidence: 98%
“…It recognized and decayed methylated mRNAs of Cyclin-A2 and kinase CDK2, thereby prolonging cell cycle progression and suppressing adipogenesis [106]. YTHDF2 plays an important role in regulating hematopoietic stem cells ex vivo expansion by regulating the stability of multiple mRNAs critical for HSC self-renewal of these cells [107]. Ythdf2 modulates neural development by promoting m6A-dependent degradation of neural development-related mRNA target [108].…”
Section: Resultsmentioning
confidence: 99%
“…In cell-based models, m 6 A has been shown to participate in numerous types of mRNA regulation, including pre-mRNA processing 17,20,21 , mRNA translation efficiency 22 , mRNA stability 16 , and miRNA biogenesis 23 . In the context of hematopoiesis, m 6 A has recently been found to regulate the expansion and self-renewal of hematopoietic stem cells 24,25 , as well as functioning as a negative regulator of myelopoiesis and a potential driver of acute myeloid leukemia (AML) 11,26 .…”
Section: Mainmentioning
confidence: 99%